2020
DOI: 10.1111/nan.12612
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: The role and contribution of transcriptional enhancers in brain cancer

Abstract: 2020) Neuropathology and Applied Neurobiology 46, 48-56 The role and contribution of transcriptional enhancers in brain cancer Genetic alterations identified across several paediatric and adult brain tumours reveal recurrent disruption of active chromatin landscapes and dysregulation of transcriptional programmes. Noncoding elements, specifically enhancers, are central to these mechanisms, and are influenced by developmental and neural gene regulatory signatures. Epigenomic and transcriptomic methods and techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Recent studies also found that SOX2 - and OLIG1 - positive progenitor cells give rise to both H3K27M DIPG and adult GBM ( 7 , 22 ). In addition, OLIG2 and RUNX2 were found to robustly segregate two distinct glioma cell populations with differential response to drug therapy ( 23 ), suggesting that these factors might contribute uniquely to therapeutic resistance ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also found that SOX2 - and OLIG1 - positive progenitor cells give rise to both H3K27M DIPG and adult GBM ( 7 , 22 ). In addition, OLIG2 and RUNX2 were found to robustly segregate two distinct glioma cell populations with differential response to drug therapy ( 23 ), suggesting that these factors might contribute uniquely to therapeutic resistance ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are numerous histone-modifying enzymes that can be categorized in writers, erasers, and readers. With regard to these chemical modifications, acetylation and methylation may be the most abundant ones when considering the currently available literature [ 30 ]. The differences in post translational modifications of histones establishes an epigenetic code and orchestrates the accessibility of the chromatin, thereby regulating transcription [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of super-enhancers has recently emerged and is an interesting model to provide an epigenetic explanation as to why certain pathways are up-regulated in cancers. Enhancers are regulators of gene expression that are several kilo bases down- or up-stream of the transcriptional start site to control transcription (loop formation) and their disruption may be an emerging therapeutic opportunity [ 30 ]. Here, we found that Mcl-1 expression correlated with the presence of a super-enhancer region in glioblastoma models, providing an explanation why this protein is increased in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…These concepts are further explored by Steve Mack and colleagues as they relate to the key consequence of epigenetic dysregulation – the disruption of key gene expression programmes[9]. In particular, they explore a common mechanism of transcriptional control that is abrogated in a range of childhood brain tumours, the concept of enhancer and super enhancer regions found outside of gene promoters, but which play a crucial role in the regulation of gene expression [10].…”
mentioning
confidence: 99%